PREVALENCE OF HELICOBACTER PYLORI IN ADMITTED PATIENT AT TERTIARY CARE HOSPITAL SWAT (Journal of Medical & Health Sciences Review, 2025)
Background: Infection caused by the bacterium Helicobacter pylori, or H. pylori, is a well-known causative agent of diseases of the gastrointestinal tract. Gastritis, gastric ulcers, and gastric cancer are just a few of the numerous diseases caused by the H. pylori bacterium. The study was intended to identify the prevalence of H. pylori infection among patients admitted to hospitals, identify the demographics and clinical features of the patients, and establish correlations among the factors of lifestyle and hygiene practices.Methods: A cross-sectional study was carried out on a tertiary care center in Swat. A total of 200 admitted patients were randomly selected from Gastroenterology, Medical, and Surgical wards. The study was done using interviews, questionnaires, medical record analysis, and lab results. Descriptive statistical methods were employed to analyze demographic information, clinical histories, and symptoms of patients. The Chi-Squared Test was used to identify any association between H. pylori infection and age, gender, intake of caffeine, hand-washing habit, and eating fast foods.Results: The prevalence of H. pylori infection was found to be 77%. Infection was more common in women (71.2%) than men (29%), with a high prevalence found among individuals aged 21-30 years (34.5%). Most patients (77%) had received previous treatment for their gastrointestinal complaints. The main complaints were loss of appetite (60%), vomiting (56%), and epigastric abdominal or burning pain (52%). There were significant correlations of H. pylori infection with age, caffeine ingestion, as well as hand-washing habits (p < 0.05), but not with fast food ingestion.Conclusion: Infection with H. pylori is found to be highly prevalent among admitted patients, and the rate is higher among young adults and women. Lack of personal hygiene and certain lifestyle habits play an important part in the transmission and development of H. pylori infection among the patients.